Environmental and Social Justice in Solid Waste Management - Christine Lutringer (Revue Internationale de Politique de Développement)
Christine Lutringer’s interview with Leo Saldanha and Bhargavi Rao reflects the pivotal role of their NGO, the Environment Support Group (ESG), in bringing about changes in practices and policies of solid waste management in Bangalore. The campaign for a new solid waste management policy, which was co-organised by ESG, underscores the significance of the legal activism initiated by civil society groups. The public interest litigation (PIL) that united the various affected parties was key to transforming the solid waste management policy of the municipality. Saldanha and Rao discuss the strategy of their NGO while showing how a progressive ruling by a court led to the decentralisation of solid waste management. They also point to the challenges of implementing the judgment and to the fact that processes of waste collection and disposal are not merely technical, administrative matters but are eminently social and cultural issues. ESG’s advocacy activities have, therefore, aimed to secure fair and respectable treatment for solid waste workers, an aspect that has otherwise been eclipsed in the public debate on waste. The interview concludes with reflections on ESG’s endeavours over the last twenty years to promote environmental and social justice in Bangalore.